Long term use of analgesics and risk of osteoarthritis progressions and knee replacement: propensity score matched cohort analysis of data from the Osteoarthritis Initiative. Issue 4 (April 2016) - Hafezi-Nejad, N.; Guermazi, A.; Roemer, F.W.; Eng, J.; Zikria, B.; Demehri, S.
Summary: Objectives: To determine the association between the long-term use of analgesics and progression of osteoarthritis (OA) as evidenced by up to 3-years follow-up worsening of radiographic Kellgren–Lawrence (KL) grade and incidence of knee replacement (KR). Design: Using nearest neighbor matching of the propensity scores with caliper in the Osteoarthritis Initiative (OAI) cohort, 173 index (Analgesic +) and 173 referent (Analgesic −) subjects were included. Analgesic + and − subjects had analgesics in all and none of their visits, respectively. Analgesic + and − subjects were balanced in their demographics, baseline, first, second and third year body mass index (BMI), Western Ontario and McMaster (WOMAC) total score, Physical and Mental health summary scales (SF-12), Physical Activity Scale for the Elderly (PASE) and Charleston Comorbidity Scale. Analgesic + and − subjects were also matched for baseline radiographic KL grade. Interval increase in the KL grade and incidence of KR were defined as the outcome. Results: Included subjects had average 6.5 years of follow-up. By the third year, 44 subjects had an interval increase in the KL grade; 29 in Analgesic + and 15 among Analgesic − subjects ( P = 0.024). By the eighth-year, 41 subjects had their first KR; 29 in Analgesic + and 12 among Analgesic − subjects ( P = 0.005). Hazard Ratio (HR) of OA progression and KR for Analgesic + subjects was 1.91 (1.02–3.57) and 2.57 (1.31–5.04), respectively. Conclusions: Long-term use of analgesics may be associated with radiographic progression of knee OA and increased risk of future KR.